The Effect of Coniferous Forest Age on Some Soil Organic Carbon Fractions in a Semiarid Ecosystem - Zerrin Kasırga; Rasim Koçyiğit (Journal of New Results in Science)
Soil organic C content in forested areas creates a greater attention for carbon sequestration and removal of atmospheric CO2 back into soil. The aim of this study was to evaluate the effect of different age of pine forest (Pinus nigra) plantation on soil organic C content and some biological carbon fractions in a semiarid ecosystem of northern Turkey. Soil samples were taken from 0 – 5, 5 – 15, and 15 – 30 cm depths of different age (7, 14, and 40 years) of adjacent forested area with three replications. Soil organic C content significantly increased in 14yr forested area compared to 7 and 40yrs forested areas (p